Optimizing Marketing Strategies Through Digital Marketing on MSME Products in the Culinary Sector in Tanggulangin District, Sidoarjo Regency - Suryono, Gatot; Fitriyah, Hadiah (CV. Media Digital Publikasi Indonesia, 2025)
The purpose of this study is to identify best practices for digital marketing of food products of micro, small, and medium enterprises (MSMEs) in Tanggulangin District, Sidoarjo Regency. The methodology used in this research is qualitative. In this study, five MSMEs in the culinary sector of Tanggulangin sub-district were surveyed-the owners of Warung Pring Bali and Warung Candi Ubud as well as Omah Kidul culinary, lesehan sawah in Kedungbanteng (LTS), and rujak cingur Tanggulangin. The research took place in these sectors. Results from interviews and focus groups were triangulated in the data analysis. Based on the findings, MSME owners in the food industry really need to master digital marketing if they want to maximize or improve their competitiveness while facing business problems. A number of micro, small and medium enterprises (MSMEs) have improved their digital marketing strategies by making good use of social media, while others still have not done so. In order for micro, small and medium enterprises (MSMEs), especially those engaged in catering services, to grow rapidly, cooperation and coordination between various parties are needed. In addition, MSME activists in Tanggulangin Subdistrict have their own obstacles due to the fierce competition in the food service sector